ON THE STATE OF FUNCTIONAL ACTIVITY OF THE SYMPATHETIC-ADRENAL SYSTEM AND FREE RADICAL PROCESSES IN WOMEN OF FERTILE AGE WITH METABOLIC SYNDROME - Tashtemirova I. M (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The aim of the given work was study interactions of impairments sympathetic – adrenal systems functional condition and processes of peroxidal oxidation of lipids in woman of fertile age with metabolic syndrome. 91 women at the age of 25-49 were observation. They were randomized into 3 groups: I (control) – 15 healthy persons, II – 39 patients with arterial hypertension, III – 37 women with arterial hypertension in combination with metabolic syndrome. The results of carried investigations showed that activation of sympathetic adrenal system and processes of peroxidal oxidation of lipids took place in metabolic syndrome. Marked lowering of sympathetic – adrenal system key ferment catecholamins (MAO monoaminooxidaze) desamidization activity and considerable activation of peroxidal oxidation of lipid products which have great significance in revealing the mechanism of metabolic syndrome development were observed in metabolic syndrome. This results in the prolonged toxic influence of catecholamins on myocardium.